Optimisation of an integrated parallel distribution system by including network marketing. Issue 2 (20th May 2020) - Shafiei, Mahdi; Modarres, Mohammad
Network marketing is a business model that depends upon a network of distributors for growth, such as in multilevel marketing. A direct selling method features independent agents that make up a distribution network for goods and services. This paper provides a framework to study the network marketing by adopting the traditional channel. To motivate all distributers in network marketing as well as retailers, it is required to design a well-balanced distribution and pricing system. The allocated commission for distributers in different layers of network marketing is part of pricing system, which is vital. In this paper, we develop an approach to determine all elements of system, including product price, wholesale price as well as commissions in network marketing simultaneously. A game model is applied to optimise the pricing and determine commission and number of layer of network marketing structure. A numerical example illustrates our proposed approach for better understanding.